Une doctrine d'abus de procédure revigorée en droit pénal canadien - Grondin, Rachel (Les Cahiers de droit, 1983)
This article examines the doctrine of abuse of process in Canadian criminal law in the light of two recent events, the decision of the Supreme Court of Canada in Amato c. R. and the adoption of the Canadian Charter of Rights and Freedoms.